Phylodynamic reconstruction of major chicken infectious anemia virus clades epidemiology, dispersal, and evolution - Franzo, Giovanni; Legnardi, Matteo; Poletto, Francesca; Baston, Riccardo; Faustini, Giulia; Cecchinato, Mattia; Tucciarone, Claudia Maria (Frontiers in Microbiology, 2025)
IntroductionImmunosuppressive diseases, such as chicken infectious anemia virus (CIAV), pose a major threat to livestock farming due to reduced disease resistance, poor vaccine response, and overall poor productivity. CIAV, recognized globally for decades, shows a significant genetic diversity, but its implications remain underexplored.MethodsThis study analyzed over 1,000 VP1 sequences and examined CIAV’s epidemiology, evolution, and spread with various phylodynamic and phylogeographic approaches.ResultsFindings suggest that CIAV likely originated in Japan in the early 20th century, followed by worldwide diversification in two main clades. Both clades exhibited no significant competition and similar global patterns, characterized by a progressive increase until about 2000, when a transient decline was observed for some years, potentially reflecting the increasing use of vaccines. Accordingly, although significant selective pressures were shaping viral evolution, comparable strengths were estimated in the two viral populations. The phylogeographic analysis identified several connections involving also distantly related regions, and more generally, multiple introduction events occurred in several countries and were followed by local evolution, indicative of unconstrained viral circulation.DiscussionOverall, the study highlights the ongoing circulation and evolution of different CIAV variants worldwide, where biosecurity measures and vaccination appear insufficient to prevent viral presence and dispersal.